185 Preventing Urinary Fistulae After Artificial Urinary Sphincter Removal: Outcomes of a Standardized Protocol. Issue 1 (1st April 2022) - Lin, J.; Ginsberg, D.; Doumanian, L.; Boyd, S.; Loh-Doyle, J.
ABSTRACT: Introduction: The artificial urinary sphincter (AUS) is the standard treatment for moderate to severe stress urinary incontinence in male patients. Despite their efficacy, the AUS is not without risk. Patients with an AUS are susceptible to complications such as mechanical failure, device infection, and urethral erosion. Erosion of the urethra can result in negative sequelae such as urethral stricture disease and urinary fistulae. Objective: While there is no debate that patients presenting with urethral erosion require removal of the AUS, there is a lack of consensus on how to manage the patient in the perioperative period. We present our experience using a standardized surgical technique and perioperative protocol used at our institution to manage patients with an AUS presenting with urethral erosion. Methods: Using an IRB-approved prosthetic database we completed a retrospective review of 97 patients who underwent AUS explantation between 2009 and 2020. Indications for removal, patient demographics, AUS component characteristics, and post-operative outcomes were analyzed. Patients undergoing AUS removal in the setting of urethral erosion were treated with a standardized protocol. Upon presentation, cystourethroscopy is performed to confirm erosion and to facilitate safe passage of a urethral catheter. With the urethral catheter in place, all AUS components are removed. After urethral cuff removal, urethrorraphy is performed. A 10-French surgical drain is placed through a separate stab incision and made to lie in the perineum and the wounds are closed in multiple layers. The urethral catheter is left in place for 4 weeks. After 4 weeks, physical examination and cystourethroscopy is performed to confirm repair of the urethra and the absence of fistula. Patients are seen monthly and are deemed eligible for reimplantation only after a minimum of 3 months have elapsed after explantation and the patient is deemed to have sufficient healthy urethra. Results: No intraoperative complications occurred during AUS explantation. 117 patients underwent AUS removal during the study period. 94 (80.3%) patients had AUS removal due to urethral erosion. After median follow-up of 18.1 months (IQR 6.5 – 48.2) after AUS removal, there were a total 6 (4.0%) patients who developed a urethrocutaneous fistula with median time from AUS removal to fistula resolution of 6.5 months. Each patient with fistulae had presented with erosion of the urethra as indication for AUS removal. 67 (57.3%) patients underwent successful AUS reimplantation after removal with median time between explant and reimplant of 3.5 months (IQR3-4.8). Risk factors for urinary fistulae include urethral erosion, prior treatment with pelvic radiotherapy, and increasing age at time of AUS removal. Conclusions: Urinary fistula can be prevented after urethral erosion with standardized surgical technique and peri-operative management in patients with an AUS. Disclosure: No